1994. Development of a Meningococcal Serogroup B Serum Bactericidal Assay Using Fetal Bovine Serum. (26th November 2018) - Kim, Han Wool; Lee, Ji Hyen; Kim, Kyung-Hyo
Abstract: Background: The quadrivalent meningococcal conjugate vaccines do not target serogroup B meningococcus (MenB), an important cause of meningitis and sepsis. MenB vaccines have been recently developed and licensed for infants and young adults. Serum bactericidal activity serves as an immunological index for evaluating the immunogenicity of vaccines. However, there is no standardized serum bactericidal assay (SBA) for MenB owing to difficulty in selecting target strains and complement sources. Using fetal bovine serum, we developed a new SBA by modifying a previous SBA for meningococcal serogroups A, C, W135, and Y and applied it to clinical samples. Methods: An isolate from an invasive disease and three reference strains were used as the target strains, and the genotypes of the antigens contained in the MenB vaccine (4CMenB) (Bexsero; GlaxoSmithKline) were determined. Non-specific killing was assessed by using baby rabbit serum, fetal bovine serum, and healthy adult serum as complement sources. Serum was obtained from clinical samples of six healthy adults before and 1 month after 4CMenB immunization. Results: The isolate and the three reference strains all contained factor H binding protein (fHBP) peptide type 1.1, which was consistent with the fHBP antigens contained in 4CMenB. The bactericidal activity in the serum (complement source) of 30 healthy adults ranged from 53% to 90%. Non-specific killing in baby rabbit serum was greater than 80%. Considering the species specificity of meningococcal fHBP, non-specific killing (82% - 91%) was similar when human factor H was added. Non-specific killing was less than 50% in fetal bovine serum, which was used as the complement source for evaluation of clinical samples. After 4CMenB immunization, the serum bactericidal indices for all the test sera were increased 4 times or more. Conclusion: We identified fetal bovine serum as a potential complement source for the MenB SBA assay. This method should be standardization using reference sera, and the putative protective SBA indices for fetal bovine serum should be determined. Disclosures: All authors: No reported disclosures.